Comparative Evaluation of Anesthetic Efficacy of Warm and Conventional 2% Lignocaine for the Success of Inferior Alveolar Nerve Block (IANB) in Mandibular Permanent Molars: A Randomized Controlled Clinical Trial - Mirza, Maha Ali; Syed Muzammil Hussain; Ajmal Yousaf; Areeba Maryam; Qurat-ul-ain Abbasi; Kanza Zafar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate and compare the anesthetic effectiveness of warm versus conventional 2% Lignocaine in achieving successful inferior alveolar nerve block (IANB) for mandibular permanent molars.Study Design: Randomized Controlled Trial (ClinicalTrials.gov: NCT06806202)Place and Duration of Study: Armed Forces Institute of Dentistry, Rawalpindi, Pakistan from Dec 2024 to Mar 2025.Methodology: A double-blind clinical trial involving 70 patients (35 in each Group) diagnosed with irreversible pulpitis was conducted to compare the efficacy of 2% Lignocaine administered at 25°C (Group A) and 42°C (Group B) for inferior alveolar nerve block (IANB). Pain during injection was evaluated using the Visual Analogue Scale (VAS), and the onset of anesthesia in seconds was determined with an electric pulp tester.Results: There was a significant difference in pain during administration of anesthesia between Group A (25°C) with median VAS score of 7.00 (IQR: 2.00) and of Group B (42°C) with median VAS score of 2.00 (IQR: 2.00) on Visual Analogue Scale (VAS) with a p-value < 0.001.  Similarly, the onset time of anesthesia in seconds was significantly shorter in Group B (42°C) with a median of 208.2 seconds (IQR: 11.34)  as compared to the Group A (25°C) with a median onset time of 286.8 seconds (IQR: 9.9) with the p-value < 0.001. ....Conclusion: Within limitation of the study it is concluded that warmed Lignocaine is more effective than Lignocaine at room temperature in reducing pain during administration and achieving faster onset of anesthesia in seconds.